Three-dimensional a-Si/a-Ge radial heterojunction near-infrared photovoltaic detector - Xiaolin Sun (Nature Portfolio, 2019)
Abstract In this work, three-dimensional (3D) radial heterojunction photodetectors (PD) were constructed over vertical crystalline Si nanowires (SiNWs), with stacked hydrogenated amorphous germanium (a-Ge:H)/a-Si:H thin film layer as absorbers. The hetero absorber layer is designed to benefit from the type-II band alignment at the a-Ge/a-Si hetero-interface, which could help to enable an automated photo-carrier separation without exterior power supply. By inserting a carefully controlled a-Si passivation layer between the a-Ge:H layer and the p-type SiNWs, we demonstrate first a convenient fabrication of a new hetero a-Ge/a-Si structure operating as self-powered photodetectors (PD) in the near-infrared (NIR) range up to 900 nm, indicating a potential to serve as low cost, flexible and high performance radial junction sensing units for NIR imaging and PD applications.